2014
DOI: 10.1242/dev.110189
|View full text |Cite
|
Sign up to set email alerts
|

Partial interchangeability of Fz3 and Fz6 in tissue polarity signaling for epithelial orientation and axon growth and guidance

Abstract: In mammals, a set of anatomically diverse polarity processesincluding axon growth and guidance, hair follicle orientation, and stereociliary bundle orientation in inner ear sensory hair cells -appear to be mechanistically related, as judged by their dependence on vertebrate homologues of core tissue polarity/planar cell polarity (PCP) genes in Drosophila. To explore more deeply the mechanistic similarities between different polarity processes, we have determined the extent to which frizzled 3 (Fz3) can rescue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…The work of Hua et al (2014) and the experiments described above, show that Frizzled and Vangl also control LP orientation on the dorsal surface of the tongue. To determine whether Celsr1 also plays a role in LP orientation, we examined flat mounts of Celsr1 -/-and Celsr1 +/-, tongues at P30 (Figure 8).…”
Section: The Lp Patterning Phenotype Produced By Inactivation Of Celsr1mentioning
confidence: 77%
See 3 more Smart Citations
“…The work of Hua et al (2014) and the experiments described above, show that Frizzled and Vangl also control LP orientation on the dorsal surface of the tongue. To determine whether Celsr1 also plays a role in LP orientation, we examined flat mounts of Celsr1 -/-and Celsr1 +/-, tongues at P30 (Figure 8).…”
Section: The Lp Patterning Phenotype Produced By Inactivation Of Celsr1mentioning
confidence: 77%
“…In previous work (Hua et al, 2014), LP on the dorsal surface of the tongue were visualized in whole mount preparations by genetic labeling with Keratin (K)17-GFP (Bianchi et al, 2005) or by systemic administration of the fixable dye AM4-65. More recently, we observed that the tongue epithelium of mice that are >2-3 weeks of age exhibit endogenous fluorescence that can be used to visualize LP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fz3 −/− ;Fz6 −/− embryos reveal redundant functions in neural tube closure and in rotationally orientating the kinocilium/stereociliary bundle complex on the apical face of inner ear sensory hair cells (Wang, Guo, & Nathans, 2006). Additionally, epidermis-specific double knockout of Fz3 and Fz6 (in K14-Cre; Fz3 CKO/CKO ;Fz6 −/− mice) reveals a redundant role for these genes in orienting the filiform papillae on the dorsal surface of the tongue (Hua, Chang, et al, 2014). Stimulated by the partial redundancy of Fz3 and Fz6 , Hua, Chang, et al (2014) asked whether this redundancy can be extended to other tissues by enlarging the domains of Fz3 and Fz6 gene expression.…”
Section: Frizzled3 and Frizzled6mentioning
confidence: 99%